2003
DOI: 10.1203/01.pdr.0000054654.73826.ac
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Dietary Sphingomyelin on Central Nervous System Myelination in Developing Rats

Abstract: Human milk contains sphingomyelin (SM) as a major component of the phospholipid fraction. Galactosylceramide (cerebroside), a metabolite of sphingolipids, increases along with CNS myelination, and is generally considered a universal marker of myelination in all vertebrates. L-Cycloserine (LCS) is an inhibitor of serine palmitoyltransferase (SPT), a rate-limiting enzyme for sphingolipid biosynthesis that is reported to show increased activity with development of the rat CNS. The present study examined the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 38 publications
1
111
0
1
Order By: Relevance
“…We have reported that dietary sphingomyelin contributes to CNS myelination in developing rats [6] . De novo synthesis of sphingolipids is initiated by serine palmitoyltransferase (SPT), which is the rate-limiting enzyme for the reaction by which serine and palmitoyl-ConA form 3-ketosphinganine ( fig.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…We have reported that dietary sphingomyelin contributes to CNS myelination in developing rats [6] . De novo synthesis of sphingolipids is initiated by serine palmitoyltransferase (SPT), which is the rate-limiting enzyme for the reaction by which serine and palmitoyl-ConA form 3-ketosphinganine ( fig.…”
Section: Introductionmentioning
confidence: 93%
“…De novo synthesis of sphingolipids is initiated by serine palmitoyltransferase (SPT), which is the rate-limiting enzyme for the reaction by which serine and palmitoyl-ConA form 3-ketosphinganine ( fig. 3 ) [6][7][8] . SPT is located in the endoplasmic reticulum and the Golgi apparatus [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Sphingolipids and metabolites Reduction of the number of aberrant crypt foci and adenocarcinomas Dillehay et al [1994] Shift in tumor type (malignant → benign) Schmelz et al [1996; Symolon et al [2004]; Spitsberg [2005] Anticholesterolemic Noh & Koo [2003; Nyberg et al [2000]; Eckhardt et al [2002] Protection of the liver from fat-and cholesterolinduced steatosis Duivenvoorden et al 2006 Suppression of gastrointestinal pathogens Sprong et al [2002]; Vesper et al [1999]; Pfeuffer & Schrezenmeir [2001] Neonatal gut maturation Oshida et al [2003] Myelination of the developing central nervous system Oshida et al [2003] Endogenous modulators of vascular function Michel et al [2007] Associated with age-related diseases and the development of Alzheimer Parodi [2001]; Spitsberg [2005] Sphingosine 1-phosphate Mitogenic Zhang et al [1990Zhang et al [ , 1991 Phosphatidyl-serine (PS) Restore normal memory on a variety of tasks McDaniel et al [2003] Positive effects on alzheimer patients Crook et al [1992]; Heiss et al [1994]; Pepeu et al [1996]; Gindin et al [1998]; Hashioka et al [2004] Improve exercise capacity of exercising humans Kingsley [2006] Phosphatidylcholine (PC) Support liver recovery from toxic chemical attack or viral damage Kidd [2002] Protects the human GI mucosa against toxic attack Anand et al [1999] Reduction of necrotising enterocolitis Carlson et al [1998] Lysophosphat-idylcholine (lyso PC) Bacteriostatic and bactericidal capacity van Rensburg et al [1992] Strong gastroprotective role in the duodenal mucosa ; ; Kivinen et al [1995] Other components Vitamin E and carotenoids Antioxidants Spitsberg [2005] as a mediator of senescence in a cell culture...…”
Section: Polar Lipidsmentioning
confidence: 99%
“…Despite of relatively small amounts, sphingolipids are signifi cant components in foods and highly essential for human health 8 . Dietary sphingolipids have benefi cial effects such as preventing cancer 9-14 , improving skin barrier 15 and contributing to central nervous system myelination 16 .…”
Section: Introductionmentioning
confidence: 99%